Single-entity coccolithophore electrochemistry shows size is no guide to the degree of calcification. Issue 2 (31st March 2022) - Yang, Minjun; Batchelor-McAuley, Christopher; Barton, Samuel; Rickaby, Rosalind E. M.; Bouman, Heather A.; Compton, Richard G.
Abstract : Controlled electrochemistry induced acid dissolution of calcifying marine phytoplankton reveals their degree of calcification. Abstract : We report single-entity measurements of the degree of calcification of individual phytoplankton cells. Electrogenerated acid is used to dissolve the calcium carbonate (CaCO3 ) shell (coccosphere) of individual coccolithophores and the changes in size are monitored by simultaneous optical measurements, allowing the CaCO3 content of the single phytoplankton cell to be inferred via analysis of the dissolution kinetics. Three species of coccolithophore, E. huxleyi, G. oceanica and C. braarudii, were studied with CaCO3 masses measured over 3 orders of magnitude ranging from 2.6 pg to 8.3 ng of CaCO3 per cell. Surprisingly, within a species, the CaCO3 content is not correlated to the size of the coccosphere but the volume of its shell. Further, the variation of the CaCO3 content with the cell size and the particulate inorganic carbon (PIC) to particulate organic carbon (POC) ratio at different stages of the growth phase is reported.